2005
DOI: 10.1097/01.ede.0000147106.32027.3e
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Fruits, Vegetables, and Dairy Products in Early Childhood and Subsequent Blood Pressure Change

Abstract: These results suggest that a diet rich in fruits, vegetables, and dairy products may have beneficial effects on blood pressure during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
109
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 19 publications
6
109
1
4
Order By: Relevance
“…Previous cross-sectional [11] and [14] and prospective [15] and [16] studies show an inverse relationship between milk or dairy product intake and cardiometabolic risk factors, in children and adolescents. It seems that milk and/or dairy product intake reduces the risk of central obesity [11] and [14], high BP [15] and [16], and insulin resistance [14].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous cross-sectional [11] and [14] and prospective [15] and [16] studies show an inverse relationship between milk or dairy product intake and cardiometabolic risk factors, in children and adolescents. It seems that milk and/or dairy product intake reduces the risk of central obesity [11] and [14], high BP [15] and [16], and insulin resistance [14].…”
Section: Discussionmentioning
confidence: 88%
“…It seems that milk and/or dairy product intake reduces the risk of central obesity [11] and [14], high BP [15] and [16], and insulin resistance [14]. However, studies examining the association between dairy product intake and clustering of cardiometabolic risk factors are limited in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased fruit and vegetable consumption early in life may have other longterm benefits. For example, a diet rich in fruits early in life may have a protective effect on cancer risk in adult [34] and a diet rich in fruits, vegetables, and dairy products during preschool years may have beneficial effects on blood pressure during childhood and adolescence [35].…”
Section: Discussionmentioning
confidence: 99%
“…Despite most measures of diet having only moderate reliability, longitudinal studies of dietary intake indicate some degree of continuity in food choices over childhood (Skinner et al, 2002;Zive et al, 2002), and even from adolescence to adulthood (Lien and Klepp, 1999;Lake et al, 2006). The Framingham Children's Study reported correlations of 0.74 and 0.66 for fruit/vegetable and dairy intake respectively, in children from ages 3 to 12 years (Moore et al, 2005).…”
Section: Introductionmentioning
confidence: 99%